Jargon Dalam Perlombaan Burung Murai Batu Di Desa Kemantran Dan Ciledug Serta Implikasinya Terhadap Pembelajaran Di SMA - Fatur Rozi Saputra; Khusnul Khotimah; Agus Riyanto (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2022)
This study aims to describe the jargon form of the stone magpie competition in Kemantran Village and describe the implications of the research results on Indonesian learning in high school. This research uses a qualitative descriptive approach. The technique of providing data in this study is to use library techniques, reading techniques, and listening and recording techniques. Data analysis in this study used the presentation of the results of data analysis using informal methods. The results showed that there are 5 forms of jargon which include (1) basic word jargon, (2) compound jargon, (3) reword jargon, (4) reword jargon, (5) acronym word jargon. The results of this study can be implied in Indonesian language learning in high school class X odd semester with basic competence X KD 3.5 evaluating anecdotal texts from the aspect of implied meaning, with material assessing the content and aspects of implied meaning in anecdotal texts class X semester 1.